COMMUNICATIVE APPROACH IN TEACHING AND LEARNING PROCESS - Мамбетова, Гулжанат (Вестник ЗКУ, 2024)
Communicative approach is used and applied as an alternative method in the process of teaching―learning that focuses on language as a medium of communication. Communication ability involves in understanding fully the vocabulary, grammar, comprehension, and all aspects of English skills such as reading, listening, speaking and writing. One main focus of the classroom action research that appears from communicative approach which is applied in the process of teaching―learning academic reading will be discussed. Communicative approach emphasizes on communication in the learning process rather than mastery of linguistic forms. Teacher’s role is to facilitate students in the communication process. While the students do a lot of practice. In addition to that, accuracy and fluency are used simultaneously. The results showed the application of communicative approach effectively improved the students’ ability such as improvement of some aspects, for example, aspects of English: vocabulary, grammar, pronunciation, communication, and ability of cooperation, collaboration, socialization, sharing ideas, opinion, and suggestion. The objective of teaching, the form of teaching―learning activity, and the kinds of learning material used by the teachers were consistent with those which were recommended by communicative approach.